Selecting a risk assessment tool to use in practice – a 10 point guide - Fazel, S; Wolf, A (BMJ Publishing Group, 2017)
With the increase in the number of risk assessment tools and clinical algorithms in many areas of science and medicine, this Perspective article provides an overview of research findings that can assist in informing the choice of an instrument for practical use. We take the example of violence risk assessment tools in criminal justice and forensic psychiatry, where there are more than 200 such instruments and their use is typically mandated. We outline 10 key questions that researchers, clinicians and other professionals should ask whether deciding what tool to use, which are also relevant for public policy and commissioners of services. These questions are based on two elements – research underpinning the external validation and derivation or development of a particular instrument. We also recommend some guidelines for reporting drawn from consensus guidelines for research in prognostic models.